Relationship Between Oral Poor Hygiene and Broken Teeth with Oral Tongue Squamous Cell Carcinoma - Fatholah Behnoud; Saadat Torabian; Maasoumeh Zargaran (Acta Medica Iranica, 2011)
Previous studies on etiology of squamous cell carcinoma (SCC) of the tongue have reported results with respect to long term exposure to cigarette smoking and alcohol abuse. The aim of this study was to investigate risk factors for SCC of the tongue in a set of patients with minimum exposure to cigarette smoking and alcohol. Sixty four cases with diagnosis of oral tongue SCC were reviewed in this study. The patients underwent surgical management at the educational and therapeutic centers, Imam and Buali Hospitals (Hamedan, Iran) between the dates of January 1990 and December 2006. Eighty five percent of patients were older than 40 years of age. Most of patients had poor oral hygiene, dental decay and halitosis. It appears that poor oral hygiene and nutritional deficiency can be considered as risk factors for the SCC of the tongue in west of Iran.